Fatigue in railway infrastructure - Robinson, Mark A.; Kapoor, Ajay (Woodhead Publishing in mechanical engineering., 2009)
Fatigue is a major issue affecting safety and quality of service in the railway industry. This book reviews key aspects of this important subject. It begins by providing an overview of the subject, discussing fatigue at the wheel-rail interface and in other aspects of infrastructure. It then considers fatigue in railway and tramway track, looking at causes of potential failure in such areas as rails and fixings as well as sleepers. It also reviews failure points in structures such as embankments and cuttings. The book analyses fatigue in railway bridges, looking in particular at masonry arch b.